VGG-16 Transfer Learning for Accurate Classification of Three Local Durian Varieties Using Leaf Morphology Images - Nuqqy Zahhar, Ahmad Haikal; Mas Diyasa, I Gede Susrama; Prami Swari, Made Hanindya (Jurnal Teknik Informatika (Jutif), 2026)
Durian (Durio zibethinus Murr), recognized as the "king of fruits" in Southeast Asia, represents a significant genetic asset for Indonesian agriculture with high economic value. East Java leads national production, contributing 580.5 thousand tons (29.59%) of the total 19.6 million tons in 2024. However, local durian quality faces persistent challenges due to minimal maintenance practices and farmers' limited expertise in variety identification. Manual taxonomic identification based on leaf morphology requires specialized knowledge, is time-consuming, and prone to subjective errors, particularly for three popular Nganjuk varieties—local, montong, and lai—which exhibit similar leaf characteristics. Previous studies have addressed durian classification using fruit images or disease detection on leaves, but a research gap exists for variety classification specifically using leaf images with deep learning approaches. This study implements VGG-16 transfer learning architecture with ImageNet pre-trained weights to classify three durian varieties based on leaf morphology images. A dataset of 600 high-resolution images (2048×2048 pixels, 200 per class) was collected from Nganjuk orchards following standardized protocols and validated by three independent experts (two experienced farmers and one plant taxonomist), achieving substantial inter-annotator agreement (Fleiss' kappa = 0.87). Preprocessing included resizing to 224×224 pixels with bilinear interpolation, normalization to [0,1], and standardization using ImageNet statistics. Data augmentation through random rotation (±30°), horizontal flipping (48.8% probability), contrast adjustment (±50.1%), and width/height shifting (±12%) expanded the dataset fourfold to 2,400 images. Using a 90:10 train-test split (2,160:240), the VGG-16 model trained with Adam optimizer (learning rate 0.001, dropout 0.5, dense layer 256 units) achieved 97.08% accuracy after 4 epochs in 1.11 minutes. Performance metrics demonstrated high precision (0.93-1.00), recall (0.92-1.00), and F1-scores (0.95-0.99) across all classes. This research advances precision agriculture informatics by providing an automated, reliable tool for durian variety identification, supporting farmers in optimal cultivation decisions, quality control, and economic value enhancement while contributing to sustainable agricultural development and the Center for Plant Variety Protection and Agricultural Licensing (PVTPP) registration systems in Indonesia.